Prognostic Significance of Cigarette Smoking in Association with Histologic Subtypes of Resected Lung Adenocarcinoma - Yi, Jung Hoon (Korean J Thorac Cardiovasc Surg, 2019)
BACKGROUND: Smokers with lung adenocarcinoma have a worse prognosis than those who have never smoked; the reasons for this are unclear. We aimed to elucidate the impact of smoking on patients’ prognosis and the association between smoking and clinicopathologic factors, particularly histologic subtypes. METHODS: We reviewed the records of 233 patients with pathologic stage T1-4N0-2M0 lung adenocarcinomas who underwent surgery between January 2004 and July 2015. The histologic subtypes of tumors were reassessed according to the 2015 World Health Organization classification. RESULTS: In total, 114 patients had a history of smoking. The overall survival probabilities differed between never-smokers and ever-smokers (80.8% and 65.1%, respectively; p=0.003). In multivariate analyses, the predominant histologic subtype was an independent poor prognostic factor. Smoking history and tumor size >3 cm were independent predictors of solid or micropapillary (SOL/MIP)-predominance in the logistic regression analysis. Smoking quantity (pack-years) in patients with SOL/MIP-predominant tumors was greater than in those with lepidic-predominant tumors (p=0.000). However, there was no significant difference in smoking quantity between patients with SOL/MIP-predominant tumors and those whose tumors had non-predominant SOL/MIP components (p=0.150). CONCLUSION: Smoking was found to be closely associated with SOL/MIP-predominance in lung adenocarcinoma. Greater smoking quantity was related to the presence of a SOL/MIP component.